National Variability in Neonatal Resuscitation Practices at the Limit of Viability - Arzuaga, Bonnie H.; Meadow, William (American Journal of Perinatology, 2014)
Objective Delivery room management of extremely premature infants is not subjected to professional regulations. In the United States, legal definitions of human viability and statutes regulating elective abortions vary by state, placing providers in an often difficult position regarding whether to attempt resuscitation when faced with the delivery of an infant of 22 to 25 weeks gestation. The objective of this study was to delineate variations in delivery room resuscitation practices of periviable infants in the United States in 2012.Study Design Electronic survey was sent to the members of American Academy of Pediatrics Section of Perinatal Medicine. Chi-square, Fisher exact test, and multivariate logistic regression were performed.Results A total of 758 surveys returned out of which 637 were complete. Overall 68% of providers consider 23-week gestation to be the youngest age that should be resuscitated at parental request, while 25-week gestation is considered by 51% to be the youngest age of obligatory resuscitation even with parental refusal. Responses varied when providers were separated into geographical regions based on the U.S. Census Bureau (p < 0.05). When provided with delivery room scenarios, parental preference significantly affected resuscitation attempts of 22 to 25 weeks, but not 26-week infants. In scenarios of periviable elective terminations, providers' personal belief systems influenced management of aborted fetuses.Conclusions Regional practice variation exists independent of specific state laws. Parental request is the most important factor to providers resuscitating 22 to 25-week infants. Providers' personal belief systems influence infant management infrequently.
Keywords: extremely premature infants; practice variation; resuscitation; physician beliefs; physician religion